Assessment of the growing threat of urban flooding: a case study of a national survey. Issue 5 (28th May 2021) - Rainey, Jayton L.; Brody, Samuel D.; Galloway, Gerald E.; Highfield, Wesley E.
ABSTRACT: Urban flooding has become a national challenge in recent years due to a variety of socio-economic and environmental changes alongside rapid land use change in flood-prone areas. Losses from acute and chronic floods have become especially problematic in low-lying urban areas, where stormwater infrastructure deterioration, population growth, and development have accelerated over the last several decades. Unfortunately, limited information is available about the extent and consequences of urban flooding. In much of the country, little is being done to address these consequences and develop plans to address problems before they get worse. A nationwide survey was created and distributed to over 1, 000 stormwater and floodplain management practitioners in both municipalities and organizations that work with municipalities. This study examines the responses from the distributed survey pertaining to what the main causes/drivers of urban flooding are and the mitigation strategies that are being currently implemented.